2015
DOI: 10.1371/journal.pone.0123510
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Self-Reported Sleep Duration in Middle-Aged and Elderly Koreans: from the Health Examinees Study

Abstract: Though various factors related to fluctuations in sleep duration have been identified, information remains limited regarding the correlates of short and long sleep duration among the Korean population. Thus, we investigated characteristics that could be associated with short and/or long sleep duration among middle-aged and elderly Koreans. A total of 84,094 subjects (27,717 men and 56,377 women) who participated in the Health Examinees Study were analyzed by using multinomial logistic regression models. To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…Fourth, the sleep questionnaire in the CHMS did not include details such as time adults and older adults in our study. These findings are consistent with previous research, [23][24][25][26] although it should be noted that the relationship between mental health and sleep is bidirectional and likely involves a complex interplay between biological and behavioural factors. 56 Notably, in contrast to studies reporting associations between lifestyle/ behavioural factors and sleep duration in adults, [22][23][24] these factors were not significant in our study, although unadjusted models suggested a possible link between current smoking and both short and long sleep in adults (Table 3).…”
Section: Strengths and Limitationssupporting
confidence: 92%
See 3 more Smart Citations
“…Fourth, the sleep questionnaire in the CHMS did not include details such as time adults and older adults in our study. These findings are consistent with previous research, [23][24][25][26] although it should be noted that the relationship between mental health and sleep is bidirectional and likely involves a complex interplay between biological and behavioural factors. 56 Notably, in contrast to studies reporting associations between lifestyle/ behavioural factors and sleep duration in adults, [22][23][24] these factors were not significant in our study, although unadjusted models suggested a possible link between current smoking and both short and long sleep in adults (Table 3).…”
Section: Strengths and Limitationssupporting
confidence: 92%
“…Potential correlates of sleep duration were identified from the existing literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26] as applicable to each age group.…”
Section: Correlatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In only SNP model results without stress and SNP x stress level terms, two SNPs (rs2238199 and rs2681749) had nominal associations with at least one obesity-related phenotype. In particular, rs2238199 showed statistically significant associations with BMI (p = 0.009), but [12]. According to their report, the prevalence of severe distress (PWI-SF ≥27) in total sample was 13.7%, and prevalence in women (15.6%) was higher than that of men (9.9%).…”
Section: Resultsmentioning
confidence: 90%